Full and simplified assessment of left ventricular diastolic function in covid‐19 patients admitted to ICU: Feasibility, incidence, and association with mortality. Issue 11 (6th October 2022) - La Via, Luigi; Dezio, Veronica; Santonocito, Cristina; Astuto, Marinella; Morelli, Andrea; Huang, Stephen; Vieillard‐Baron, Antoine; Sanfilippo, Filippo
Abstract: Purpose: Left ventricular diastolic dysfunction (LVDD) is associated with poor outcomes in the intensive care unit (ICU). Nonetheless, precise reporting of LVDD in COVID‐19 patients is currently lacking and assessment could be challenging. Methods: We performed an echocardiography study in COVID‐19 patients admitted to ICU with the aim to describe the feasibility of full or simplified LVDD assessment and its incidence. We also evaluated the association of LVDD or of single echocardiographic parameters with hospital mortality. Results: Between 06.10.2020 and 18.02.2021, full diastolic assessment was feasible in 74% ( n = 26/35) of patients receiving a full echocardiogram study. LVDD incidence was 46% ( n = 12/26), while the simplified assessment produced different results (incidence 81%, n = 21/26). Nine patients with normal function on full assessment had LVDD with simplified criteria (grade I = 2; grade II = 3; grade III = 4). Nine patients were hospital‐survivors (39%); the incidence of LVDD (full assessment) was not different between survivors ( n = 2/9, 22%) and non‐survivors ( n = 10/17, 59%; p = .11). The E/e' ratio lateral was lower in survivors (7.4 [3.6] vs. non‐survivors 10.5 [6.3], p = .03). We also found that s' wave was higher in survivors (average, p = .01). Conclusion: In a small single‐center study, assessment of LVDD according to the latest guidelines was feasible in three quarters of COVID‐19 patients. Non‐survivors showed a trend toward greater LVDD incidence; moreover, they had significantly worse s' values (all) and higher E/e' ratio (lateral).